Water requirement and water productivity for sorghum crop in rainfed areas of Sennar State, Sudan - Mohamoud, Mohamoud A.; Yousif, Lotfie; Elhag, Muna M.; Abdalla, Abdalla S. (Gezira Journal of Agricultural Science; Vol 19 No 2 (2021), 2023)
Sorghum is one of the main crops grown under rainfed conditions in Sennar state, Sudan. However, both within the same season and between the seasons the rainfall amount is quite irregular. It is important to understand how rainfall amount and its distribution during the growing season affect water requirements and grain yield of sorghum in order to improve selection and management of cultural practices. The objective of this study was to determine the water requirement and water productivity of sorghum crop in the areas of Sennar State under three farming systems. A field experiment was conducted in two agroecological zones in Sennar State during two consecutive seasons 2014/2015 and 2015/2016. The first location was a semi-arid zone (Sennar research station farm). The second location was a semi-humid zone (Abu Naama research station farm). The experiment consisted of conventional farming system (CF), conservation agriculture (CA) and water harvesting system (WH). The sorghum variety Arfa Gadamac-8 was sown. The collected data included rainfall and weather data in addition to sorghum grain yield. The CROPWAT 8.0 computer software program was used to compute the crop water requirement (ETc). Reference evapotranspiration (ET0) and crop coefficient (Kc) were also calculated. The average values of ET0 during the growing season ranged between 3.29 and 4.4 mm/day in semi-arid zone and between 3.75 and 3.95 mm/day in semi-humid zone, for the seasons 2014/2015 and 2015/2016, respectively. The results showed that the overall average values of Kc during the initial, development, mid-season stage and late-season stage were 0.30, 0.63, 0.91 and 0.64, respectively. The results revealed that the average water requirements for sorghum crop was 2663 and 2390 m3/ha in semi-arid and semi-humid zones, respectively. The overall average values of water productivity for sorghum crop in semi-arid zone was 0.79 kg/m3 and it was 0.96 kg/m3 in semi-humid zone. Conservation agriculture and water harvesting were the best cropping systems compared to the conventional farming for sorghum production in rainfed areas of Sennar State. Investigation on water requirement and water productivity of other sorghum varieties in rainfed is needed. الإحتياجات المائية وكفاءة استخدام المياه لمحصول الذرة الرفيعة في المناطق المطرية لولاية سنار، السودان محمود عبدالله محمود 1 ولطفي عبدالرحمن يوسف 1 ومنى محمد الحاج 3 وعبدالله سليمان عبدالله 3 1 هيئة البحوث الزراعية، برنامج بحوث الهندسة الزراعية، سنار، السودان 2 هيئة البحوث الزراعية، برنامج بحوث الهندسة الزراعية، شمبات، السودان 3 قسم الهندسة الزراعية، كلية العلوم الزراعية ، جامعة الجزيرة ود مدني، السودان الخلاصة تعتبر الذرة الرفيعة من المحاصيل الرئيسية التي تزرع تحت ظروف الأمطار في ولاية سنار، السودان. كمية الأمطار في الولاية غير منتظمة، سواء في نفس الموسم أو بين الفصول. وعليه من الضروري فهم تأثير كمية الأمطار وتوزيعها خلال موسم النمو على الاحتياجات المائية وكفاءة اسنخدام المياه لمحصول الذرة الرفيعة، من أجل المساعدة في اختيار العمليات الفلاحية المناسبة. الهدف من هذه الدراسة هو تحديد الاحتياجات المائية وكفاءة اسنخدام المياه لمحصول الذرة الرفيعة في بئتين مختلفتين في ولاية سنار تحت ثلاثة نظم زراعية. أجريت تجربة حقلية في موقعين مختلفين في ولاية سنار خلال موسمين متتاليين 2014/2015 و 2015/2016. الموقع الأول هومزرعة محطة بحوث سنار (المنطقة شبه الجافة). الموقع الثاني هو مزرعة محطة بحوث أبو نعامة (المنطقة شبه الرطبة). تألفت التجربة من نظام الزراعة التقليدية(CF) ، ونظام الزراعة الحافظة (CA) ونظام حصاد المياه (WH) استخدم في التجربة صنف الذرة الرفيعة أرفع قدمك-8. شملت البيانات التي تم جمعها الأمطار والبيانات المناخية بالإضافة إلى إنتاجيةالحبوب من الذرة الرفيعة. استخدم برنامج CROPWAT 8.0لحساب الاحتياجات المائيةللمحصول (ET c ) علاوة على ذلك، تم حساب البخرنتحالمرجعي (ET o ) ومعامل المحصول(K c ) . أشارت النتائج أن متوسط ​​قيم K c خلال المرحلة الأولية، والتطوير، ومنتصف الموسم، ومرحلة ونهاية الموسم كانت 0.30 ، 0.63 ، 0.91 و 0.64 على التوالي. أوضحت النتائج أن متوسط ​​الاحتياجات المائية لمحصول الذرة بلغ 2663 و 2390 متر 3 / هكتار في المناطق شبه القاحلة وشبه الرطبة على التوالي. كانت القيم المتوسطة لكفاءة اسنخدام المياهلمحصول الذرة الرفيعة في المنطقة شبه القاحلة 0.79 كجم/متر 3 و0.96 كجم/متر 3 في المنطقة شبه الرطبة. إن نظامي الزراعة الحافظة وحصاد المياه هما الأفضل مقارنة بالزراعة التقليدية لإنتاج الذرة الرفيعة في المناطق المطرية في ولاية سنار. من الضروري تحديد الاحتياجات المائية وكفاءة استخدام مياه الأمطار للأصناف الاخرى للذرة المطري.